ChemInform Abstract: Palladium‐Catalyzed peri‐Selective Chalcogenation of Naphthylamines with Diaryl Disulfides and Diselenides via C—H Bond Cleavage. Issue 18 (May 2015) - Iwasaki, Masayuki; Kaneshika, Wataru; Tsuchiya, Yuta; Nakajima, Kiyohiko; Nishihara, Yasushi
Abstract The picolinamide moiety acts as directing group for the selective formation of peri‐thiolated and peri‐selenated products.